Diseño de un sensor de campo magnético mediante el estudio de la corriente inducida para detectar descargas atmosféricas. - Naula Allaica, Sandra Maribel (2020)
In this project, it develops a prototype magnetic field sensor to detect lightning applying the principle of induced current. First, models of detectors used in preliminary investigations by different authors linked to the study of atmospheric phenomena were studied. Also, commercial atmospheric discharge detectors were studied to interpret the principle of operation of these and their applications. The design parameters of the detector that were obtained from previous studies such as the shape of the antenna, its size, the number of winding turns and the construction material. It was define to use a square-shaped loop antenna because it has a higher reception range to variations of magnetic fields, in which the magnetic which is produced by the source of EF (Electromagnetic Fields) is induced, in the antenna winding. The signal then enters a circuit in which frequencies less than 10 kHz and higher than 15 kHz are discriminated against. The signal processing is done with Arduino Mega, and it is also the communication channel with the LabView interface in which the behavior of the magnetic field and the count of field variations against a reference (set-point) is graphically displayed. The latter is stored in the form of data with date, time and the corresponding magnetic field value. Regarding the constructive aspects of the sensor housing and antenna cover, the use of noncorrosive material such as polyethylene was considered, as it has excellent resistance to degradation caused by actions of microorganisms. Also, it has a 4 GB microSD, with the ability to store 10435 data and LiPo batteries with 18- hour autonomy. The prototype was validated using the EMF450 standard sensor for magnetic field registers in power installations such as substations and transmission lines obtaining errors of less than 2.20%. In the case of the recording of magnetic field variations, it was validated in the High Voltage Laboratory, using a transformer for disruption tests, assuming that the disruption point emulates the change in the magnetic field by the effect of a discharge 7 out of 10 downloads. Finally, the applications of the built prototype are: first, to assess the isoceraunic level of a particular area of the country. On the other hand, measuring magnetic fields in elements of electrical power systems such as electrical substations, transmission lines, transformation cameras and any electrical equipment or machinery that generates magnetic fields in the sensor measurement range (0 to 5 microteslas).There are many different beneficiaries in this project such as the electricity sector to the agricultural and livestock sectors of the country, if the work continues to guide it to the updating of isoceraunic levels in the areas of influence.